Fluorescein Angiographic Findings of Peripheral Retinal Vasculature after Intravitreal Conbercept versus Ranibizumab for Retinopathy of Prematurity - Enzhong Jin; Hong Yin; Yufei Gui; Juan Chen; Jian Zhang; Jianhong Liang; Xiao-xin Li; Mingwei Zhao (Journal of Ophthalmology)
Purpose. To evaluate angiographic findings of peripheral retina vasculature in retinopathy of prematurity (ROP) neonates who received intravitreal conbercept (IVC) or ranibizumab (IVR). Methods. Fluorescein angiography (FA) findings were retrospectively evaluated for ROP neonates who received IVC or IVR. Outcome measures included peripheral avascular zone, vascular leakage, vascular blunting, vascular loops, vascular dilatation, arteriovenous shunt, and capillary dropout. Results. Fifty-four eyes (28 patients) with ROP were included. Twenty-nine eyes (15 patients) received IVC, and 25 eyes (13 patients) received IVR. For infants of the IVC group, the mean gestational age, birth weight, and postmenstrual age (PMA) at the initial treatment were 28.96 ± 2.36 weeks, 1168.8 ± 344.5 g, and 41.22 ± 4.39 weeks, respectively. For the IVR group, they were 28.83 ± 2.34 weeks, 1255.0 ± 356.9 g, and 39.42 ± 2.77 weeks, respectively (P=0.817, 0.522, and 0.075). For the IVC group, FA performed at 71.29–115.43 weeks PMA showed 96.55% of eyes had avascular zone; vascular leakage was found in 24.14% eyes; vascular blunting, vascular dilation, vascular loops, arteriovenous shunt, and capillary dropout were found in 96.55%, 72.41%, 79.31%, 48.28%, and 68.97% eyes, respectively. For the IVR group, FA performed at 65.57–133.71 weeks PMA showed 92.0% of eyes had avascular zone; vascular leakage was found in 40.0% eyes; vascular blunting, dilatation, loops, arteriovenous shunt, and capillary dropout were found in 100%, 60.0%, 64.0%, 36.0%, and 68.0% eyes, respectively. Conclusion. No significant difference can be observed between the IVC group and IVR group for peripheral vascular structure anomalies with FA evidence. FA studies should be considered to assess the status of the peripheral retinal vasculature to determine therapeutic outcomes and potential functional outcomes.